Valoración de la seguridad en el proceso de administración de medicamentos utilizando un sistema automatizado de dispensación - Rodriguez Perez, Maribel (UMA Editorial, 2018)
The objective of this study is to calculate the prevalence of errors between a unit dose system, compared to an Automated Dispensing System (ADS) in the phases of the drug therapy process, including prescription, transcription, dispensing and administration of medication in a general hospital to determine the safety and efficiency of the automated system. Cross-sectional study carried out in a general service hospital in San Juan, Puerto Rico. The error categories by severity level have been established by NCCMERP. These serve as guidelines for organizations and health systems to categorize the types of harm that healthcare personnel can cause a patient during the treatment process. The categories are described as follows⁷: categories A, B, C and D cause no harm, and categories E, F, G, H and I indicate harm and classify it as temporary, permanent, or potentially life threatening.The independent variable of this study was the prevalence of medication errors. The dependent variable was medication errors in ADS, classified by NCCMERP categories. As defined by the NCCMERP, a medication error is “any preventable event that may cause or lead to inappropriate medication use or patient harm while the medication is in the control of the health care professional, patient, or consumer. Such events may be related to professional practice, health care products, procedures, and systems, including prescribing, order communication, product labeling, packaging, and nomenclature, compounding, dispensing, distribution, administration, education, monitoring, and use”. The study consisted of all phases of the drug therapy chain with both medication dispensing systems: unit dose and ADS. The ADS established by the hospital, as well as the unit dose system, work through manual prescription.
Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 23. To measure the error level, types of error, where the error occurs and prevalence, a descriptive analysis was undertaken based on central tendency and dispersion measures. An inferential analysis was performed using student’s t test for quantitative variables, chi square and binary logistic regression for qualitative variables. A multivariant analysis was carried out to identify possible confounding variables and identify predictive factors. Data was collected from 487 patients for the ADS and 514 patients for the unit dose system, for a total of 1,001 patients with medication error reports. The median age in this study was 63 for men and 68 for women. This study identified a distribution of medication errors of 1,507 errors in the phases of the drug therapy process. 1,175 of these corresponded to the prescription process, representing 78%. A total of 160 errors were identified under the medication administration phase, representing 10.6%; followed by the transcription stage with 104 errors, corresponding to 6.9%. The lowest percentage of errors was observed for the dispensing phase, for a total of 68 errors, representing 4.5%. Several types of errors were found in the drug therapy chain. ADS decentralized medication distribution systems have been recommended as one potential mechanism to improve efficiency and patient safety, and they are now widely used in many hospitals. The results of the present study show that the amount of medication error is less when using the ADS in all phases of the drug therapy process, except for the prescription phase. In all other phases of the drug therapy process, presenting the results for the ADC first, the percentages were as follows: transcription (25.05% vs 75.0%), dispensing (23.75% vs. 76.35%) and administration (28.1% vs 71.9%). In this study, the most commonly prescribed medications were: Humalog, Lovenox and Lantus, which belong to the insulin and anticoagulant drug classes. The ISMP established a list of potentially confusing pairs of drug names: Humalog/Humulin, Lovenox/Levemir and Lantus/Lente. It also established a list of high alert medications, which can cause severe harm when used by mistake, including death. This study allowed to establish that technology and its integration into the drug therapy process for safe medication use, as well as change in procedures, minimize the incidence and impact of harm to the patient, thus ensuring reliable health services. Implementation of new technology, such as ADS, standardized the medication administration processes, decreased turnaround time for processing medication orders, increased accuracy of medication administration to patients, and reports benefits, such as cost savings, reduction in the overall weekly stockout percentage, and estimated cost avoidance attributed to the reduced potential for product expiration.¹3,¹⁴ This is an aspect that can be studied in a future research in the Puerto Rican context. In other words, the increase of technology introduction promotes efficiency, quality and safety in healthcare. Errors can occur at any point of the drug therapy process. The results of our study show that the amount of medication errors decreases when using the ADS in all phases of the drug therapy process except for the prescription phase. For nursing professionals, ADS use can help reduce or eliminate delays due to medication availability, missing doses, and time-consuming controlled substance counts. In conclusion, the use of the ADC is more efficient and reduces errors in the therapeutic drug chain. The use of ADC is an optimal practice for improving patient safety.
Keywords: Medicamentos - Administración - Tesis doctorales; Errores en la medicación; Sistema automatizado de dosificación